A brief review of laser-induced breakdown spectroscopy for human and animal soft tissues: pathological diagnosis and physiological detection. Issue 3 (16th March 2021) - Wang, Qianqian; Xiangli, Wenting; Teng, Geer; Cui, Xutai; Wei, Kai
Abstract: Laser-induced breakdown spectroscopy (LIBS) is a promising element detection technique that has been rapidly developed for use in various applications, including the biomedical field. The technique has strong potential to analyze molecularly complex clinical specimens, for instance, human and animal soft tissues. In this work, we review the applications of LIBS in the classification and identification of soft tissues with emphasis on sample preparation and data processing. These applications can be divided into two categories, namely, pathological diagnosis and physiological detection. LIBS has been successfully used to distinguish ex vivo malignant and normal tissues, and classify the different normal tissues. Thus, LIBS may be an effective tool with potential applications in cancer diagnosis and laser surgery. This review then suggests possible development directions for further research on LIBS testing of soft tissue based on our summary and analysis of key results. Extensive studies should be implemented in a manner consistent with clinical requirements to expand the practical applications of LIBS in the future.